Reconstructing the Ontological Structure of Wujūd in Mullā Ṣadrā’s Philosophy as a Foundation for Contemporary Islamic Ecological Ethics - Syahrul Kirom; Ahmad Asmuni; Mustopa Mustopa (Sekolah Tinggi Agama Islam Sadra, 2026)
The global environmental crisis not only reflects technical and policy failures but also reveals an ontological problem in understanding the human–nature relationship. The discourse on Islamic environmental ethics remains predominantly normative-textual, centered on the concepts of khalīfah and mīzān, without sufficient metaphysical grounding, thereby creating a gap between normative sources and the ontological legitimacy of ecological ethics. This study aims to reconstruct the concept of wujūd in the philosophy of Mullā Ṣadrā as an ontological foundation for the formulation of contemporary Islamic ecological ethics. This research constitutes a qualitative study based on library research, employing philosophical and hermeneutical analysis of texts. Data was collected through documentary study encompassing relevant primary and secondary sources. Data analysis was conducted systematically through stages of conceptual identification, thematic reduction and classification, and the formulation of conclusions grounded in argumentative coherence. The findings demonstrate that the reconstruction of wujūd as a graded and dynamic ontological reality reconfigures the conceptual basis of the human–nature relationship, shifting it from an anthropocentric dualism toward an integrated existential continuum. The results further indicate that ecological ethics can be formulated as an ontological consequence of the structure of reality rather than as an external normative system. The reinterpretation of the concepts of khalīfah and mīzān within the horizon of existential yields principles of participation, ontological responsibility, and cosmic harmony as the foundation of environmental ethics. This study contributes to strengthening the metaphysical basis of Islamic environmental ethics and to advancing Islamic philosophical discourse in response to the global ecological crisis.